Historyk wobec zacierania śladów przeszłości - białe plamy w historii gospodarczej Ziemi Lubuskiej w czasach PRL = A historian confronting the erasure of the past - blank spots in the economic history of the Lubuskie Region in the PRL era - Bujkiewicz, Zbigniew (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper aims to draw attention to the concealment and destruction of economic documents by the authorities of People`s Republic of Poland (PRL). The consequences of these actions and their impact on scientific research on the Lubuskie Region are illustrated with examples of the state of the economy in the years 1945-1947, as well as the "brick yielding action" that took place from 1951 to 1956.
Keywords: Ziemia Lubuska; demontaż fabryk; akcja uzysku cegły; Lubuskie Region; dismantling of factories; brick yielding action